THE ROLE OF THE UNITED STATES AGENCY FOR INTERNATIONAL DEVELOPMENT IN HUMANITARIAN ASSISTANCE IN BORNO STATE, NIGERIA - AMINU MUSA; BENJAMIN SUNDAY ATAWODI; RABIU MUHAMMAD ISHAQ; ABUBAKAR SHEHU TARASA (International Studies Journal)
Nigeria is experiencing one of the longest-standing humanitarian crises, worsened by the rise of extremist groups like Boko Haram, armed banditry, changes in climate, poverty, and lack of development infrastructure. In Borno State, the devastating nature of humanitarian crises created the need for humanitarian interventions. Different international organisations have keyed in to render their assistance. One of the organizations providing humanitarian assistance to Borno State is the United States Agency for International Development. Although literature on humanitarian assistance in Borno State abounds, but role of USAID has not been adequately studied. It is against this backdrop that this paper investigates the role of USAID as an International governmental organization in humanitarian intervention in Borno state, Nigeria. This paper utilized qualitative method of data collection based on analysis of interview responses. Secondary source was also used in sourcing for data through a qualitative approach and conducted semi-structured interviews with 15 participants, including USAID staff, partners, beneficiaries, local authorities, and other humanitarian actors. It analysed the data using thematic analysis. The study has shown that in the face of the prevalence of humanitarian crises, USAID assistance has been very effective. The paper however recommends that USAID should continue to prioritize its engagement in Borno State and if possible, extend it to some other parts of Nigeria.